Airway plaque presenting after alteration of immunosuppression in a pediatric patient remote from heart transplantation. (24th August 2017) - Ryan, Thomas D.; Absalon, Michael J.; de Alarcon, Alessandro; Gupta, Anita; Peters, Anna L.; Lorts, Angela; Danziger‐Isakov, Lara A.; Chin, Clifford
Abstract: Success after solid organ transplantation is dependent on the proper balance of immunosuppression to prevent rejection of the allograft while limiting the risk of developing infections and malignancy. We present a 9‐year‐old girl, remote from transplant, who presented with airway plaque after a change in immunosuppression to include the mTOR inhibitor sirolimus. Differential diagnosis included direct medication side effect, infection, and neoplasia.